2016
DOI: 10.2298/bah1604369d
|View full text |Cite
|
Sign up to set email alerts
|

Infection with Strongyloides papillosus in sheep: Effect of parasitic infection and treatment with albendazole on basic haematological parameters

Abstract: The aim of this study was to determine and evaluate the basic haematological parameters in conditions of natural infection of sheep with Strongyloides papillosus, as well as after the administration of antihelminthic albendazole (ABZ). Based on the intensity of infection with S. papillosus the sheep were divided into three groups: mild, moderate and high, and after that the sheep received a single dose of ABZ of 5mg/kg per body weight, per orally. Sampling of faeces and blood for parasitologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…in the organism of mammals is followed by decrease in erythrocytes. At the same time, the lowest parameters were observed in the animals with high infestation intensity, and the number of neutrophils and eosinophils increased to 44.2 ± 2.5% and 13.3 ± 0.6% respectively with high intensity of strongyloidiasis of animals (Dimitrijević et al, 2016).…”
Section: Introductionmentioning
confidence: 82%
“…in the organism of mammals is followed by decrease in erythrocytes. At the same time, the lowest parameters were observed in the animals with high infestation intensity, and the number of neutrophils and eosinophils increased to 44.2 ± 2.5% and 13.3 ± 0.6% respectively with high intensity of strongyloidiasis of animals (Dimitrijević et al, 2016).…”
Section: Introductionmentioning
confidence: 82%
“…The development of pre-parasitic stage of Strongyloides spp. is in the feces or soil and infects cattle via skin penetration or oral through contamination of feed and water (Dimitrijevic et al, 2016). Animals can also be infected with Strongyloides spp.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Opatrny, Snell [20]stated that AST and ALT were increased by albendazole because benzimidazoles are metabolized by the liver causing a decrease in liver oxidase systems and a greater inhibition of microtubulin dependent processes could leading to a great inflammation and toxicosis of hepatocytes. Furthermore, Dimitrijevic, Jovic [31] noted that albendazole and its metabolites accumulated in in the cell causing injury because it is very fat soluble drug. Additionally, Rivera, McClearen [32] connected the use of benzimidazole as albendazole and fenbendazole therapy in rabbits with hepatic enzyme elevation.…”
Section: Discussionmentioning
confidence: 99%
“…Guengerich [42] and Dimitrijevic, Jovic [31] indicated that the biotransformation of albendazole passed through a series of reactions on CYP and FMO (reduction, protonation, addition of oxygen, hemolytic splitting of oxygen, etc.) reactive species of oxygen (ROS) and nitrogen (RNS) are generated.…”
Section: Discussionmentioning
confidence: 99%